Digitalisasi Pemantauan Tumbuh Kembang Balita Menggunakan Timbangan Pintar Berbasis IoT di Posyandu Hargomulyo - Mulasari, Surahma Asti; Tentama, Fatwa; Ghozali, Fanani Arief; Sadad, Sulthan Ghazy; Sade, Rahmadan Oktryando Putra; Arsa, Gema Samodra Cahya; Suwartini, Iis; Muslim, Farid (CV. Rayyan Dwi Bharata, 2026)
Monitoring toddler growth and development is a crucial component in accelerating stunting reduction. However, manual recording at integrated health posts (Posyandu) leads to a high risk of measurement errors, delays in data processing, and inaccurate interpretation of nutritional status. This community service activity aims to improve measurement accuracy and the efficiency of Posyandu services through the implementation of Internet of Things (IoT)-based Smart Scales at five Posyandus in Hargomulyo Village. The program included training on digital scales, training on growth and development monitoring applications, nutrition education, and pre-post evaluation of cadre knowledge. Results showed an increase in cadre knowledge and skills in digitally collecting and processing growth and development data. All cadres showed improved scores after the training, particularly in understanding the application and use of digital scales. Service digitization has been shown to improve data consistency, expedite service delivery, and strengthen early detection of stunting risk. These findings indicate that IoT technology is worthy of replication as an innovation for strengthening basic health services in rural areas.Keywords: stunting, Posyandu, IoT, digital anthropometry, health cadres